Parallel Precarity: : A Comparison of U.S. and Canadian Agricultural Guestworker Programs - Weiler, Anelyse M; Sexsmith, Kathleen; Minkoff-Zern, Laura-Anne (The International Journal of Sociology of Agriculture and Food, 2021)
As national borders tighten against undocumented migrants, agricultural employers throughout North America have pushed governments for easier access to a legalized temporary farm workforce. Some U.S. farmers and policymakers are seeking to expand the country’s temporary agricultural guest worker program (H-2A visa). Canada’s longstanding Seasonal Agricultural Worker Program has been proposed on an international scale as an example of best practices because it fulfills employer demands for a stable workforce, enables state control over migration flows and, at least on paper, safeguards workers’ rights. However, researchers have documented systemic violations of workers’ rights in both countries. How do outcomes for legalized temporary migrant farmworkers in Canada compare to those in the United States? This paper addresses an empirical gap in the literature by rigorously comparing agricultural guest worker programs in Canada and the United States. We analyze how guestworker immigration policies shape migration flows, along with employment and well-being outcomes for agricultural workers. Ultimately, we argue that programs in both countries function by creating an unfree workforce. Despite differences in the policy environment and structure of the programs, they present similar outcomes of systemic precarity for participating workers.